Peningkatan Motivasi Belajar Materi Iman Kristiani melalui Model Jigsaw di SMPN 8 Ngabang - Kristina Meni; Nerita Setianingtiyas (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
This Classroom Action Research was motivated by concerns over the competitive atmosphere that often characterizes conventional education systems. In many schools, students are conditioned to compete with one another from an early stage, reflecting the philosophy of